Conceptualising postgraduate training in biotechnology at Universities of Technology - Fossey, Annabel (South African Journal of Higher Education, 2016)
Universities of Technology are mandated to provide career-orientated programmes preparing graduates for the workplace, doing research aimed at identifying societal and industrial needs, and finding solutions. Universities of Technology interweave technology with university endeavours; focusing on the know-how for the fabrication of things, and the skill to manage fabricated products. These universities are well placed to offer qualifications in biotechnology. Biotechnology encompasses many technologies using living organisms, their parts and products for commercial purposes. The development of the biotechnology is a national priority and enjoys support from government and funding bodies in South Africa. Challenges faced by educational systems include, curricular content and pedagogies in the rapidly changing biotechnology landscape, diversity of entering students, and expectations of the industry. Graduate attributes were devised and used to devise postgraduate curricula for biotechnology at Universities of Technology following an embedded approach. A flexible integrated curriculum is proposed that addresses student diversity and industry needs. Keywords: Biotechnology, disciplinary graduate attributes, generic graduate attributes, curriculum, spiral curriculum, postgraduate qualifications.